Study Protocol: Randomised Controlled Trial Assessing the Efficacy of Strategies Involving Self-Sampling in Cervical Cancer Screening - Caroline Lefeuvre; Caroline Lefeuvre; Hélène De Pauw; Anne-Sophie Le Duc Banaszuk; Adeline Pivert; Adeline Pivert; Alexandra Ducancelle; Alexandra Ducancelle; Franck Rexand-Galais; Marc Arbyn; Marc Arbyn (International Journal of Public Health, 2022)
Objectives: The cervical cancer screening coverage remains moderate (60%) in France. The aim of the study is to evaluate the efficacy of two experimental invitation strategies (offer of urine or vaginal self-sampling kits) to reach under-screened populations and compare them with the current invitation strategy in rural departments (low medical density and low participation rate) in France.Methods: The study is a randomised controlled trial with three arms: a control arm (conventional invitation letter) and two experimental arms (mailing of a urine or vaginal self-sampling kit). The target population includes women aged 30–65 years, who had no screening test recorded since more than 4 years and who did not respond to an invitation letter within 12 months before. The primary outcome measure is the participation rate in each arm. A team of psychologists will also investigate attitudes and experiences by semi-structured/focus-group interviews with voluntary CapU4 participants and with health professionals.Result and conclusion: CapU4 will identify effective strategies to reach women not responding to current screening invitations and will generate information about acceptance of self-sampling among women and health professionals.